The Effect of Service Quality on Patient loyalty: a Study of Pri-vate Hospitals in Tehran, Iran - E Zarei; A Rahimi Forushani; A Rashidian; SM Ghazi Tabatabaei; M Arab (Tehran University of Medical Sciences, 2012)
Background: Service quality is perceived as an important factor for developing patient's loyalty. The aim of this study was to determine the hospital service quality from the patients' viewpoints and the relative importance of quality dimensions in predicting the patient's loyalty. Methods: A cross-sectional study was conducted in 2010.The study sample was composed of 943 patients selected from eight private general hospitals in Tehran. The survey instrument was a questionnaire included 24 items about the service quality and 3 items about the patient's loyalty. Exploratory factor analysis was employed to extracting the dimensions of service quality. Also, regression analysis was performed to determining the relative importance of the service quality dimensions in predicting the patient's loyalty. Result: The mean score of service quality and patient's loyalty was 3.99 and 4.16 out of 5, respectively. About 29% of the loyalty variance was explained by the service quality dimensions. Four quality dimensions (Costing, Process Quality, Interaction Quality and Environment Quality) were found to be key determinants of the patient's loyalty in the private hospitals of Tehran. Conclusion: The patients' experience in relation to the private hospitals' services has strong impact on the outcome variables like willingness to return to the same hospital and reuse its services or recommend them to others. The relationship between the service quality and patient's loyalty proves the strategic importance of improving the service quality for dragging and retaining patients and expanding the market share.